1995
DOI: 10.1042/bj3080321
|View full text |Cite
|
Sign up to set email alerts
|

Endoproteolytic processing of recombinant proalbumin variants by the yeast Kex2 protease

Abstract: The yeast Kex2 protease is regarded as the prototype of the eukaryotic family of subtilisin-like serine proteases involved in processing after dibasic amino acid sequences. Here we investigate the specificity of Kex2 using recombinant human proalbumin variants. Proalbumins with the processing site sequences Arg-Arg and Lys-Arg were cleaved after the dibasic sequence at approximately the same rate by Kex2 in vitro, and yeast expressing either of these sequences secreted mature albumin into the culture medium. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…3A, lane 2). This was despite the iacubations with proalbumin having a 33-fold higher enzy-] le : substrate ratio compared to the assays with the synthetic " able 2 l, inetic parameters for processing by Yap3 peptides, A number of natural proalbumin variants (-2Arg ~ His, -1Arg ~ Gln, -2Arg--* Cys, + 1Asp ~ Val) [17] and recombinant proalbumin variants (-4Val~Arg, -2Arg ~ Lys, -4Val ~ Arg-2Arg ~ His, + 1Asp ~ Arg) [10] were also tested as substrates for Yap3 (not shown). Yap3 did not release the propeptide from any of these variants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3A, lane 2). This was despite the iacubations with proalbumin having a 33-fold higher enzy-] le : substrate ratio compared to the assays with the synthetic " able 2 l, inetic parameters for processing by Yap3 peptides, A number of natural proalbumin variants (-2Arg ~ His, -1Arg ~ Gln, -2Arg--* Cys, + 1Asp ~ Val) [17] and recombinant proalbumin variants (-4Val~Arg, -2Arg ~ Lys, -4Val ~ Arg-2Arg ~ His, + 1Asp ~ Arg) [10] were also tested as substrates for Yap3 (not shown). Yap3 did not release the propeptide from any of these variants.…”
Section: Resultsmentioning
confidence: 99%
“…The reactions were stopped after 16 h by the addition of pepstatin A to 50 gg/ml. Proalbumin was incubated with Kex2 as previously described [10]. Reactions were analysed in 1% agarose gels using Trisbarbital buffer pH 8.6 [14].…”
Section: Assays With Proalbumin and Albuminmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive analyses of its specificity (15,(22)(23)(24) have revealed that substrates containing multiple basic residues surrounding the scissile bond are cleaved with high efficiencies. The nature of this specificity is not completely understood even though molecular modeling (Protein Data Bank code 1YPS) (24) has revealed that yapsin 1 has a more open active site compared with other aspartyl proteases and that many of its subsites are electronegative, thus allowing for the accommodation of positively charged residues within and surrounding the cleavage site (24).…”
Section: Discussionmentioning
confidence: 99%
“…Variants of the pre-pro-a-F with different amino acid changes in the vicinity of the pro-region processing site (Table 1) were designed on the basis of the earlier research (Bevan et al 1998;Ledgerwood et al 1995;Rholam et al 1995;Rockwell and Fuller 1998;Suzuki et al 2000). Corresponding coding DNA fragments were synthesized by PCR using Pfu DNA polymerase (Fermentas) and then cloned and sequenced on the pPH93 vector as in-frame fusions with the L-chain gene.…”
Section: Methodsmentioning
confidence: 99%